GLOBALISASI PERUBAHAN SOSIAL BUDAYA DAN KRISIS MULTIDIMENSI DI INDONESIA - Riwanto (Widyadari : Jurnal Pendidikan, 2021)
Globalization is a worldwide phenomenon, so that no country on earth has been able to avoid it. This process is marked by the existence of fundamental changes in various fields of life, which greatly affect the pattern of life of a nation. As is happening in Indonesia, socio-cultural changes take place suddenly (rapidly), triggering a crisis in the form of: relative depression, dislocation, disorientation, and negativism. The crisis that occurred in Indonesia originated from the repressive conditions in the era of the New Order regime which created a stagnant democratic life, then developed into a monetary crisis, an economic crisis, a moral crisis and now a multidimensional crisis. This condition makes the Indonesian people unprepared and less enthusiastic in facing the free market era, which must be viewed as a reality that cannot be negotiated any longer.